Expression of Galectin-1, Galectin-3 and T-Antigen in Breast Carcinoma Tissues and its Significance in Axillary Lymph Node Infiltration - Remani2, K. Sujathan1*, Thara Somanathan1, P. (Recent Research in Science and Technology, 2011)
Galectins are a family of low molecular weight Ã¯ÂÂ¢Ã¯â‚¬Â Ã¯â‚¬Â galactoside specific endogenous lectins with functions in cell growth, cell activation, cell–cell, cell–matrix adhesion including binding to carcinoembryonic antigen, laminin and metalloprotenase. Gal-3 by interacting with T- antigen has been found to enhance metastatic potential of human tumors in a number of experimental studies. We correlated the endogenous expression patterns of Gal-1, Gal-3 along with their respective binding sites and T- antigen expression of breast cancer tissues of lymph node positive cases with that of lymph node negative cases. A lower cytoplasmic expression of Gal-3 and a higher expression of T- antigen were found to differentiate lymph node positive cases from node negative cases, suggesting that Gal-3 and T- antigen expression analysis can have a role to predict lymph node metastasis in breast cancer patients. Further detailed analysis to explore the significance of these markers in breast cancer is warranted.